2018
DOI: 10.1103/physrevc.98.044621
|View full text |Cite
|
Sign up to set email alerts
|

Nonlocal interactions in the (d,p) surrogate method for (n,γ) reactions

Abstract: Background Single-neutron transfer reactions populating states in the continuum are interesting both for structure and astrophysics. In their description often global optical potentials are used for the nucleon-target interactions, and these interactions are typically local. In our work, we study the effects of nonlocality in (d, p) reactions populating continuum states. This work is similar to that of [1] but now for transfer to the continuum.Purpose A theory for computing cross sections for inclusive process… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 34 publications
(93 reference statements)
0
6
0
Order By: Relevance
“…Starting with the fully relaxed tetrahex-C structure, uniaxial tensile strain up to 40% at an increment of 1% is applied in either the x (zigzag) or y (armchair) direction to explore its strainstress relation and determine ideal strength (the highest strength of a crystal at 0 K) [32,33] and critical strain (at which ideal strength reaches) [22]. The tensile strain is defined as,…”
Section: Methodsmentioning
confidence: 99%
“…Starting with the fully relaxed tetrahex-C structure, uniaxial tensile strain up to 40% at an increment of 1% is applied in either the x (zigzag) or y (armchair) direction to explore its strainstress relation and determine ideal strength (the highest strength of a crystal at 0 K) [32,33] and critical strain (at which ideal strength reaches) [22]. The tensile strain is defined as,…”
Section: Methodsmentioning
confidence: 99%
“…Even though in their most general form, optical potentials are non-local, many reaction models have not been adapted to deal with this non-locality. It has been shown that non-locality affects strongly transfer observables [17][18][19][20][21][22][23]. Since these studies were limited to low energy, in this work we investigated the importance of these effects in the higher energy regime, the regime for which knockout reactions are typically measured.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last few years, a large body of work demonstrates that including non-locality explicitly in the optical potential significantly affects the calculated reactions observables [17][18][19][20][21][22][23]. These studies have focused primarily on (d, p) transfer reactions in the energy range E lab < 50 MeV.…”
Section: Introductionmentioning
confidence: 99%
“…Typically charge-exchange reactions to the IAS are studied within 1-step DWBA. Models that incorporate more complex reaction dynamics explored in other reac-tion channels, such as transfer reactions and Coulomb dissociation (see [15][16][17][18][19]), could present relevant extensions for improving the theory of charge-exchange reactions to IAS. More importantly, given the advances in uncertainty quantification for reactions [20][21][22][23], it is imperative to quantify the uncertainties in the charge-exchange predictions from theory.…”
Section: Introductionmentioning
confidence: 99%